Investigation of Borrow Pit TEA28 BP3, Fenstanton, Cambridgeshire, UK - W.A. Boismier; E. Allison; C. Ardis; R. Banerjea; C.R. Batchelor; P. Dark; K. Dudgeon; C.P. Green; E. Henderson; J. Ladocha; J. Weinstock; D.S. Young; et al. (Internet Archaeology)
This report provides a synthesis of the results for a Palaeolithic watching brief carried out at Borrow Pit TEA28 BP3 (NGR TL 3020 6779) as part of the A14 Cambridge to Huntingdon road improvement scheme. A number of Late Pleistocene deposits was identified, recorded and sampled for environmental remains. Samples were also taken for optically stimulated luminescence dating (OSL) and accelerator mass spectrometry radiocarbon dating (AMS). Vertebrate remains and a very small assemblage of seven lithic artefacts were also collected from some of them.